Karakteristik pasien tuberkulosis paru yang menjalani program pengobatan di Bandar Lampung - Sri Suharti; Dimas Ning Pangesti (Holistik Jurnal Kesehatan, 2021)
Patient characteristics on the intensive phase treatment among patients with pulmonary tuberculosis in Bandar LampungBackground: Pulmonary tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. Based on data got from the Kemiling Health Center in 2019 there were 38 respondents.Purpose: To find out the patient characteristics on the intensive phase treatment among patients with pulmonary tuberculosis in Bandar LampungMethod: A quantitative approach, the sample was 38 respondents diagnosed with pulmonary tuberculosis on the intensive phase treatment in the public health center. Data collection using interview techniques with questionnaires and analyzed using the chi-square test.Results: Finding the respondents' BMI and LILA in meanwhile, from the results of the LILA measurement with 38 respondents, the result is that 15 (38.5%) was underweight, while 23 (60.5%) was normal. The correlation of all variable characteristic with the intensive phase treatment finding p-value ≥ 0.05.Conclusion: The all of variable characteristic has no relation with the intensive phase treatment.Keywords : The intensive phase treatment; Patients; Pulmonary tuberculosisPendahuluan : Tuberkulosis paru (TB) adalah penyakit infeksi menular kronik yang disebabkan oleh kuman Mycobacterium tuberculosis. Berdasarkan data yang diperoleh  dari Puskesmas Kemiling pada tahun 2019 berjumlah 38 orang.Tujuan : Mengetahui karakteristik pasien selama pengobatan fase intensif pada penderita tuberkulosis paru di Bandar LampungMetode : Pendekatan kuantitatif, sampel sebanyak 38 responden yang terdiagnosis tuberkulosis paru pada perawatan fase intensif di Puskesmas. Pengumpulan data menggunakan teknik wawancara dengan kuesioner dan dianalisis menggunakan uji chi-square.Hasil: Didapatkan IMT dan LILA pada responden hasil pengukuran LILA dengan 38 responden didapatkan hasil bahwa 15 (38,5%) tergolong underweight, sedangkan 23 (60,5%) tergolong normal. Korelasi semua karakteristik variabel dengan perlakuan fase intensif menemukan p-value ≥ 0.05.Simpulan : Semua karakteristik variabel tidak ada hubungannya dengan menjalani program pengobatan.